PEMODELAN PENGELOMPOKKAN PRESTASI DOSEN MENGGUNAKAN METODE FUZZY C-MEANS - Sri Redjeki (JURNAL INFORMATIKA DAN KOMPUTER, 2017)
A college desperately needs valid information about the existing learning process. A piece of information will have more value when processed using existing methods in mining data. This is because data mining can provide accurate results and can be used as a means for quick and precise decision making especially related to the behavior of lecturers in the learning process. This research will do modeling for lecturer achievement classification using Fuzzy C-Means.This research object is done at one of private universities in Yogyakarta. The input parameters used in the FCM method are teaching attendance, final score completion and questionnaire results from students. Input of 3 variables is called independent variable, while the value of lecturer achievement index (IPAD) as the dependent variable. Group of achievement determined in this research there are 3 that is good, medium and less. The data used are 59 lecturers. The results of the research indicate that FCM can be used to model lecturer achievement where most lecturers are in the cluster category good for all variables used in this research. The results of the questionnaire variables have a significant result to the IPAD lecturer semester of 2009/2010.